2013
DOI: 10.1080/02692171.2013.838544
|View full text |Cite
|
Sign up to set email alerts
|

The labour market and the distribution of earnings: an empirical analysis for Italy

Abstract: Using four waves of data from the Participation Labour Unemployment Survey, a database of information on the Italian labour market supply, we address the question of earnings dispersion by applying a "nested" decomposition procedure of the Theil inequality measure, which combines into a unified framework the standard decompositions by population subgroups and income sources. The empirical evidence obtained points to the key role played by the self-employees in shaping labour income inequality, especially at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…However, the INAPP-PLUS survey provides individual weights to account for nonresponse and attrition issues which usually affect sample surveys. Similarly to other empirical studies relying on the same dataset (see, among others, Clementi and Giammatteo 2014;Filippetti et al 2019;Radicchia (2011, 2016), all descriptive statistics and estimates reported in this analysis are weighted using those individual weights. 5 The second survey composing our innovative dataset is the 2013 wave of the ICP, created in 2004 and currently performed by INAPP.…”
Section: Data and Descriptive Statisticsmentioning
confidence: 99%
“…However, the INAPP-PLUS survey provides individual weights to account for nonresponse and attrition issues which usually affect sample surveys. Similarly to other empirical studies relying on the same dataset (see, among others, Clementi and Giammatteo 2014;Filippetti et al 2019;Radicchia (2011, 2016), all descriptive statistics and estimates reported in this analysis are weighted using those individual weights. 5 The second survey composing our innovative dataset is the 2013 wave of the ICP, created in 2004 and currently performed by INAPP.…”
Section: Data and Descriptive Statisticsmentioning
confidence: 99%
“…4 The INAPP-PLUS survey also provides individual weights to account for non-response and attrition issues which usually affect sample surveys. Similarly to other empirical studies relying on the same dataset (see, among others, Clementi and Giammatteo, 2014;Filippetti et al, 2019;Meliciani 4 The stratification of the INAPP-PLUS survey sample is based on population strata by NUTS-2 Region of residence, urbanisation degree (i.e., metropolitan or non-metropolitan area), age group, sex, and employment status (i.e., employed, unemployed, student, retired, or other inactive status).…”
Section: Datamentioning
confidence: 79%
“…3 Data and descriptive statistics this dataset (see, among others, Bonacini et al, 2021;Clementi and Giammatteo, 2014;Esposito and Scicchitano, 2020;Filippetti et al, 2019;Meliciani and Radicchia, 2011;Van Wolleghem et al, 2019), we report descriptive statistics and estimates by weighting all observations with such individual weights.…”
Section: Conceptual Framework and Relevant Literaturementioning
confidence: 99%